Empirical Modelling And Experimental Investigation On Absorption Spectra Of Colloidal Metal Nanoparticles And Quantum Dots Suspended In Ionic Surrounding Media - Mehrdel, Baharak (2019)
This study investigates the influence of the nanoparticle size and refractive index of non-absorbent ionic surrounding media on the optical absorption spectra of noble metal nanoparticles (Au, Ag; excited emission) and semiconductor quantum dots (CdSe/ZnS; spontaneous emission) designed for sensing application.